Liberalizing trade in environmental goods and services - Dijkstra, Bouwe; Mathew, Anuj (Springer Verlag, 2015)
We examine the effects of trade liberalization in environmental goods in a model with one domestic downstream polluting firm and two upstream firms (one domestic, one foreign). The upstream firms offer their technologies to the downstream firm at a flat fee. The domestic government sets the emission tax rate after the outcome of R&D is known. The effect of liberalization on the domestic upstream firm's R&D incentive is ambiguous. Liberalization usually results in cleaner production, which allows the country to reach higher welfare. However this increase in welfare is typically achieved at the expense of the environment (a backfire effect).